Analysis of Effective Learning Strategies to Improve Intercultural Understanding in the School Environment: SMAN 1 Lembar - Rahmat Setiawan; Dita Septiana Ultami; Ernawati; Eyin Puspita Sari; Hesti Nila Kusnita; Sawaludin (al-Afkar, Journal For Islamic Studies, 2026)
This study aims to analyze the level of students' intercultural understanding, challenges in implementing multicultural education, and multicultural-based learning strategies at SMAN 1 Lembar. This study used a mixed methods method with a questionnaire survey, in-depth interviews, and a systematic literature review. The results show that the majority of students have a good understanding of cultural diversity, although cross-cultural awareness still needs to be improved. Programs such as the Pancasila Student Profile Strengthening Project (P5) and Saturday Culture have a positive influence on students' intercultural understanding, but further development is needed. Multicultural-based learning strategies in PPKn subjects have proven effective through heterogeneous group discussions, case studies, and culture-based learning media. This study recommends the integration of multicultural education in the curriculum, teacher training, and strengthening of culture-based programs to create an inclusive and tolerant learning environment, in accordance with the principles of the Pancasila Student Profile.